MANAGEMENT ACCOUNTING AND PARTNERSHIP-BASED COMMUNITY ECONOMIC EMPOWERMENT MODELS IN THE SOCIETY 5.0 ERA - Ermawati, Yuli; Pujianto; Mardiana, Fitra (Sekolah tinggi ilmu ekonomi pemuda, 2024)
In facing the Era of Society 5.0, society is required to innovate through the local industrial sector and prepare itself to compete globally. The partnership pattern as a Community Economic Empowerment Strategy through MSMEs must be addressed wisely by large business actors and MSMEs by carrying out collaboration that is mutually reinforcing and beneficial for the progress and welfare of MSME actors which will have a positive impact on the community's economy. Empowerment will be very effective through four main factors, namely Human Resources, Government Role, Business Capital, and Partnerships. The aim of this research is to identify partnership-based empowerment in research objects, identify the implementation of Management Accounting in research objects, and create a model of community economic empowerment (MSMEs) to face the era of society 5.0. The research method used is descriptive qualitative. The results of the research show that the community economic empowerment provided by the Government (Dinkopdag), a private company (Astra International Tbk), and a facilitator (Wijaya Putra University) to KBA Semanggi Surabaya is in accordance with the partnership pattern to answer challenges in the era of society 5.0 but has not yet fully reached Management Accounting concept in empowerment programs for MSMEs. Researchers found a partnership-based community economic empowerment model that can synergize stakeholders with the community from all components of community organizations